INTERNAL DETERMINANTS OF THIRD-PARTY FUNDS MOBILIZATION IN INDONESIAN ISLAMIC RURAL BANKS (2020–2024) - Aldika Bayu Setiawan; Rini Safitri (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2026)
This study examines the effect of promotional costs, education and training costs, and the number of offices on Third-Party Funds (DPK) in Indonesian Islamic Rural Banks (BPRS). The study employs a quantitative approach using monthly time-series data consisting of 60 observations from 2020–2024 obtained from the Sharia Banking Statistics published by the Financial Services Authority. Data analysis includes the Augmented Dickey-Fuller (ADF) stationarity test and Multiple Linear Regression Analysis. The results indicate that all variables are stationary at the “level”. Partially, the results of the study showed that the promotional costs did not have a significant impact on third-party funds (sig. 0.112). On the other hand, the cost of education and training and the number of offices have a positive and significant effect on third-party funds with significance values of 0.005 and 0.000, respectively. Simultaneously, the results of the F test showed a significance value of 0.000, which proves that the three independent variables together have a significant effect on the BPRS third-party funds in Indonesia.